Analisis Diversifikasi Konsumsi Energi Menurut Pola Pangan Harapan dan Faktor-Faktor yang Mempengaruhinya - Mewa Ariani; Handewi P. Saliem (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 1999)
EnglishThis paper aims at to analyse diversification pattern of energi consumption and its influences. Data National Socio-economic Survey (SUSENAS) 1993 an 1996 collected by Central Beaure of Statistics (BPS) is used in this study. The results of this study were (1) level of energy consumption tend to decrease between 1993-1996 and still under consumption of requirement energy (2.150 calory/cap/day); (2) Compared in